Genetically engineered pigs manifesting pancreatic agenesis with severe diabetes. Issue 2 (30th November 2020) - Nagaya, Masaki; Hasegawa, Koki; Watanabe, Masahito; Nakano, Kazuaki; Okamoto, Kazutoshi; Yamada, Takeshi; Uchikura, Ayuko; Osafune, Kenji; Yokota, Harumasa; Nagaoka, Taiji; Matsunari, Hitomi; Umeyama, Kazuhiro; et al.
Abstract : Introduction: Pancreatic duodenum homeobox 1 ( Pdx1 ) expression is crucial for pancreatic organogenesis and is a key regulator of insulin gene expression. Hairy and enhancer of split 1 ( Hes1 ) controls tissue morphogenesis by maintaining undifferentiated cells. Hes1 encodes a basic helix loop helix (bHLH) transcriptional repressor and functionally antagonizes positive bHLH genes, such as the endocrine determination gene neurogenin-3. Here, we generated a new pig model for diabetes by genetic engineering Pdx1 and Hes1 genes. Research design and methods: A transgenic (Tg) chimera pig with germ cells carrying a construct expressing Hes1 under the control of the Pdx1 promoter was used to mate with wild-type gilts to obtain Tg piglets. Results: The Tg pigs showed perinatal death; however, this phenotype could be rescued by insulin treatment. The duodenal and splenic lobes of the Tg pigs were slender and did not fully develop, whereas the connective lobe was absent. β cells were not detected, even in the adult pancreas, although other endocrine cells were detected, and exocrine cells functioned normally. The pigs showed no irregularities in any organs, except diabetes-associated pathological alterations, such as retinopathy and renal damage. Conclusion: Pdx1-Hes1 Tg pigs were an attractive model for the analysis of pancreatic development and testing of novel treatment strategies for diabetes.